The Influence of Physical Fitness, Nutritional Status, Parental Attention, and Learning Interest on the Learning Outcomes of Physical Education, Sports and Health - Apriandi, Apriandi; Masrun, Masrun; Khairuddin, Khairuddin; Putra, Aldo Naza (JETL (Journal of Education, Teaching and Learning), 2024)
This type of research aims to analyze the influence of physical fitness, nutritional status, parental attention, and interest in learning on the learning outcomes of Physical Education, Sports, and Health students of SMKN 1 Pangkalan Kuras, Pelalawan Regency. The background of the study shows that student learning outcomes are still low, with an average completeness of only 58%. This is allegedly related to physical fitness, nutritional status, parental attention, and students' interest in learning. The research method uses a quantitative approach with path analysis to measure the direct and indirect influence between variables. The study population was students of SMKN 1 Pangkalan Kuras, and data was collected through physical fitness tests, nutritional status measurements, and questionnaires on parental attention and interest in learning. The results showed that physical fitness, nutritional status, parental attention, and interest in learning significantly affected learning outcomes, both individually and simultaneously. Learning interest has been proven to play a role as a mediator that strengthens the relationship between physical fitness, nutritional status, and parental attention to learning outcomes. This study concludes that a holistic approach involving physical health, family support, and learning motivation is essential to improve student learning outcomes. The implication of this research is the need for collaboration between teachers, parents, and schools in creating a conducive learning environment, supporting health, and encouraging students' interest in learning